Evaluation of the diagnostic value of transcranial electrical stimulation (TES) to assess neuronal functional integrity in horses - Journée, Sanne Lotte; Journée, Henricus Louis; Bergmann, Wilhelmina; Chantziaras, Ilias; Vanderperren, Katrien; Raes, Els; Reed, Stephen Michael; de Bruijn, Cornelis Marinus; Berends, Hanneke Irene; Delesalle, Cathérine John Ghislaine (Frontiers in Neuroscience, 2024)
Medical imaging allows for visualization of spinal cord compression sites, however, it is impossible to assess the impact of visible stenotic sites on neuronal functioning, which is crucial information to formulate a correct prognosis and install targeted therapy. It is hypothesized that with the Transcranial Electrical Stimulation (TES) technique neurological impairment can be reliably diagnosed. Objective: to evaluate the ability of the TES technique to assess neuronal functional integrity in ataxic horses by recording TES induced Muscular Evoked potentials (MEPs) in three different muscles and to structurally involve multiple ancillary diagnostic techniques, such as clinical neurological examination, plain radiography (RX) with ratio assessment, contrast myelography and post-mortem gross and histopathological examination. Methods: Nine ataxic horses, showing combined fore and hindlimb ataxia (grade 2-4) were involved, together with 12 healthy horses. TES induced MEPs were recorded bilaterally at the level of the trapezius (TR), the extensor carpi radialis (ECR) and tibialis cranialis (TC) muscles. Two Board certified radiologists evaluated intra- and intersagittal diameter ratios on RX, reductions of dorsal contrast columns and dural diameters (range skull-T1). Post mortem gross pathological and segmental histopathological examination was also performed by a Board certified pathologist. Results: TES-MEP latencies were significantly prolonged in both ECR and TC in all ataxic horses as opposed to the healthy horses. The TR showed a mixed pattern of normal and prolonged latency times. TES-MEP amplitudes were least discriminative between healthy and ataxic horses. Youden’s cutoff latencies for ataxic horses were 24.6 ms for the ECR and 45.5 ms for the TC (sensitivity and specificity of 100%). For healthy horses, maximum latency values were respectively 22 and 37ms. RX revealed spinal cord compression in 8 out of 9 involved ataxic horses with PPVs of 0-100%. All ataxic horses showed multi-segmental Wallerian degeneration. All pathological changes recorded in the white matter of the spinal cord were widely dispersed across all cervical segments, whereas grey matter damage was more localized at specific segmental level. Conclusion. TES-MEP latencies have a high sensitivity to detect impairment of spinal cord motor functions for mild to severe ataxia (grade 2-4).